Involvement of the R2R3-MYB transcription factor MYB21 and its homologs in regulating flavonol accumulation in Arabidopsis stamen. (8th April 2021) - Zhang, Xueying; He, Yuqing; Li, Linying; Liu, Hongru; Hong, Gaojie
Abstract: Commonly found flavonols in plants are synthesized from dihydroflavonols by flavonol synthase (FLS). The genome of Arabidopsis thaliana contains six FLS genes, among which FLS1 encodes a functional enzyme. Previous work has demonstrated that the R2R3-MYB subgroup 7 transcription factors MYB11, MYB12, and MYB111 redundantly regulate flavonol biosynthesis. However, flavonol accumulation in pollen grains was unaffected in the myb11myb12myb111 triple mutant. Here we show that MYB21 and its homologs MYB24 and MYB57, which belong to subgroup 19, promote flavonol biosynthesis through regulation of FLS1 gene expression. We used a combination of genetic and metabolite analysis to identify the role of MYB21 in regulating flavonol biosynthesis through direct binding to the GARE cis -element in the FLS1 promoter. Treatment with kaempferol or overexpression of FLS1 rescued stamen defects in the myb21 mutant. We also observed that excess reactive oxygen species (ROS) accumulated in the myb21 stamen, and that treatment with the ROS inhibitor diphenyleneiodonium chloride partly rescued the reduced fertility of the myb21 mutant. Furthermore, drought increased ROS abundance and impaired fertility in myb21, myb21myb24myb57, and chs, but not in the wild type or myb11myb12myb111, suggesting that pollen-specific flavonol accumulation contributes to drought-induced male fertility by ROS scavenging in Arabidopsis. Abstract : MYB21 modulates the accumulation of flavonols through directly binding to the GARE cis -element of the FLS1 promoter, which is essential for the reduced-fertility phenotype of the myb21 mutant.